Long-Term Effects of Whole-Body Vibration on Human Gait: A Systematic Review and Meta-Analysis - Fischer, Matthieu; Vialleron, Thomas; Laffaye, Guillaume; Fourcade, Paul; Hussein, Tarek; Chèze, Laurence; Deleu, Paul-André; Honeine, Jean-Louis; Yiou, Eric; Delafontaine, Arnaud (Frontiers in Neurology, 2019)
Background: Whole-body vibration is commonly used in physical medicine and neuro-rehabilitation as a clinical prevention and rehabilitation tool. The goal of this systematic review is to assess the long-term effects of whole-body vibration training on gait in different populations of patients. Methods: We conducted a literature search in PubMed, Science Direct, Springer, Sage and in study references for articles published prior to 7 December 2018. We used the keywords “vibration,” “gait” and “walk” in combination with their Medical Subject Headings (MeSH) terms. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was used. Only randomized controlled trials (RCT) published in English peer-reviewed journals were included. All patient categories were selected. The duration of Whole-Body Vibration (WBV) training had to be at least 4 weeks. The outcomes accepted could be clinical or biomechanical analysis. The selection procedure was conducted by two rehabilitation experts and disagreements were resolved by a third expert. Descriptive data regarding subjects, interventions, types of vibration, training parameters and main results on gait variables were collected and summarized in a descriptive table. The quality of selected studies was assessed using the PEDro scale. Statistical analysis was conducted to evaluate intergroup differences and changes after the WBV intervention compared to the pre-intervention status. The level of evidence was determined based on the results of meta-analysis (effect size), statistical heterogeneity (I2) and methodological quality (PEDro scale). Results: A total of 859 studies were initially identified through databases with 46 articles meeting all of the inclusion criteria and thus selected for qualitative assessment. Twenty-five studies were included in meta-analysis for quantitative synthesis. In elderly subjects, small but significant improvements in the TUG test (SMD = −0.18; 95% CI: −0.32, −0.04) and the 10MWT (SMD = −0.28; 95% CI: −0.56, −0.01) were found in the WBV groups with a strong level of evidence (I2 = 7%, p = 0.38 and I2 = 22%, p = 0.28, respectively; PEDro scores ≥5/10). However, WBV failed to improve the 6MWT (SMD = 0.37; 95% CI: −0.03, 0.78) and the Tinetti gait scores (SMD = 0.04; 95% CI: −0.23, 0.31) in older adults. In stroke patients, significant improvement in the 6MWT (SMD = 0.33; 95% CI: 0.06, 0.59) was found after WBV interventions, with a strong level of evidence (I2 = 0%, p = 0.58; PEDro score ≥5/10). On the other hand, there was no significant change in the TUG test despite a tendency toward improvement (SMD = −0.29; 95% CI: −0.60, 0.01). Results were inconsistent in COPD patients (I2 = 66%, p = 0.03), leading to a conflicting level of evidence despite a significant improvement with a large effect size (SMD = 0.92; 95% CI: 0.32, 1.51) after WBV treatment. Similarly, the heterogeneous results in the TUG test (I2 = 97%, p < 0.00001) in patients with knee osteoarthrosis make it impossible to draw a conclusion. Still, adding WBV treatment was effective in significantly improving the 6 MWT (SMD = 1.28; 95% CI: 0.57, 1.99), with a strong level of evidence (I2 = 64%, p = 0.06; PEDro score ≥5/10). As in stroke, WBV failed to improve the results of the TUG test in multiple sclerosis patients (SMD = −0.11; 95% CI: −0.64, 0.43). Other outcomes presented moderate or even limited levels of evidence due to the lack of data in some studies or because only one RCT was identified in the review. Conclusions: WBV training can be effective for improving balance and gait speed in the elderly. The intervention is also effective in improving walking performance following stroke and in patients with knee osteoarthrosis. However, no effect was found on gait quality in the elderly or on balance in stroke and multiple sclerosis patients. The results are too heterogenous in COPD to conclude on the effect of the treatment. The results must be taken with caution due to the lack of data in some studies and the methodological heterogeneity in the interventions. Further research is needed to explore the possibility of establishing a standardized protocol targeting gait ability in a wide range of populations.